2019
DOI: 10.21203/rs.2.15642/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cryptococcal antigenemia and its predictors among HIV infected patients in resource limited settings: a systematic review

Abstract: Background : Cryptococcosis is an opportunistic fungal infection that primarily affects people with advanced Human immunodeficiency virus (HIV) disease and is an important cause of morbidity and mortality around the globe. By far the most common presentation of the disease is cryptococcal meningitis (CM), which leads to an estimated 15-20% of all HIV related deaths worldwide, 3/4 of which are in sub-Saharan Africa. However, to the best of our knowledge there is quite limited reviewed data that on the epidemiol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The risk of exposure to HIV infection was heterosexual contact for all patients, except for one case (a 14-yearold boy). CD4 lymphocyte counts for female and male patients ranged from 9-205 cells/ mm 3 (mean= 59.0, SD=73.4) and 4-212 cells/ mm 3 (mean=41.8, SD=50.8), respectively [38] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of exposure to HIV infection was heterosexual contact for all patients, except for one case (a 14-yearold boy). CD4 lymphocyte counts for female and male patients ranged from 9-205 cells/ mm 3 (mean= 59.0, SD=73.4) and 4-212 cells/ mm 3 (mean=41.8, SD=50.8), respectively [38] .…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that in a developing country like ours, tuberculosis still remains as the most common co-infection in PLHIV. In a review study by Derbie et al (2020), a total of 8338 HIV positive individuals were reported in 22 studies conducted in ten different countries during 2007-2018. Most articles reported the mean CD4 count of participants below 100 cells/μL.…”
Section: Discussionmentioning
confidence: 99%
“…Azithromycin is currently widely used as the first-line drug for the treatment of mycoplasma pneumonia [22,23]. Expect it, azithromycin has a wide range of antibacterial activities against pneumococcus, staphylococcus aureus, anaerobic bacteria, gram-negative bacteria, gram-positive bacteria, and has a certain inhibitory effect on chlamydia pneumoniae, chlamydia humanoid and chlamydia trachomatis [24]. Nevertheless, long-term use of azithromycin can increase the incidence of adverse reactions in different tissues of patients, such as skin, respiratory, digestive and nervous systems [25].…”
Section: Discussionmentioning
confidence: 99%